Public Administration Ethics Education to Build Anti-Corruption Integrity among Students of SMP N 13 Padang - Roni Ekha Putera; Tengku Rika Valentina; Tirza Haqia Purnama (Warta Pengabdian Andalas, 2024)
The high level of corruption, which has become a pathology in developing countries, especially Indonesia, is evidenced by the 2022 international transparency data, which scored 34/100 and ranked 110 out of 180 surveyed countries. Indonesia ranks as the 5th most corrupt country in Southeast Asia. With these results, Indonesia has only been able to increase its Corruption Perception Index (CPI) score by 2 points from 32 over the past decade since 2012. Despite Law No. 20 of 2001's eradication of corruption, which covers various aspects, related to anti-corruption efforts, including education and anti-corruption socialization, this pathology remains unresolved. Therefore, a strong foundation is needed, especially among the younger generation as the nation's future leaders, by strengthening students' character regarding integrity and courage against corruption. This community engagement used socialization, interviews with school members, and participatory observation within the school environment. The concept of public administration ethics serves as the basis for this activity. The results showed that anti-corruption education through the perspective of public administration at SMP N 13 Padang plays a significant role in shaping students' integrity and courage in combating corruption. As adolescents, students are in the process of forming moral values and behaviors. Thus, anti-corruption education interventions can significantly impact shaping their character. Students improved their understanding of corruption and developed a more courageous attitude and strong integrity. The results provided valuable insights and a foundation for further improvement in anti-corruption education in middle schools.